Tumor Necrosis Factor-α Mediates One Component of Competitive, Experience-Dependent Plasticity in Developing Visual Cortex - Kaneko, Megumi; Stellwagen, David; Malenka, Robert C.; Stryker, Michael P. (Neuron (Cambridge, Mass.), 2008)
Rapid, experience-dependent plasticity in developing visual cortex is thought to be competitive. After monocular visual deprivation, the reduction in response of binocular neurons to one eye is matched by a corresponding increase to the other. Chronic optical imaging in mice deficient in TNFα reveals the normal initial loss of deprived-eye responses, but the subsequent increase in response to the open eye is absent. This mutation also blocks homeostatic synaptic scaling of mEPSCs in visual cortex in vitro, without affecting LTP. In monocular cortex, thought not to be subject to competition, responses in TNFα mutants are as reduced as in the binocular zone. Pharmacological inhibition of endogenous TNFα in wild-type mice phenocopies the knockout. These findings suggest that experience-dependent competition in developing visual cortex is the outcome of two distinct, noncompetitive processes, a loss of deprived-eye responses followed by an apparently homeostatic increase in responses dependent on TNFα signaling.